Assessment of Raw Leachate Characteristics and Its Pretreatment by Lime - Ali Zazouli, Mohammad; Maleki, Afshin; Izanloo, Hasan (Asian Journal of Chemistry, 2010)
The aims of this research are to determine heavy metals (Ni, Cd, Cr, Zn and Cu) and COD concentration in municipal solid waste leachate in Isfahan city (Iran) and to examine the application of precipitation process for pretreatment of raw leachates. Jar-test technique was employed in order to determine the optimum dosages and pH for the removal of COD and heavy metals. Lime was tested as precipitant. The results showed that leachate pH was 4.2-6.8 mgL-1 and the average was 5.25 ± 0.53 mg L-1. The mean concentration of COD, total solids, Cd, Cr, Cu, Zn and Ni in raw leachate samples was 40157 ± 6052, 41025 ± 5985, 0.63 ± 0.64, 1.22 ± 0.91, 2.15 ± 1.71, 7.42 ± 5.78 and 2.22 ± 1.48 as mg L-1, respectively. The concentration of measured pollutants was more than effluent standard limits of Iran EPA. The results of precipitation tests in optimum conditions showed that the removal efficiencies of heavy metals and COD were 79-88 % and 25 %, respectively. Also the residues of heavy metals after treatment get to under of guideline limits. The results have indicated optimum pH was 9.5. Also the effective coagulant dosage was 2.4 g L-1. So, lime may be used as a useful pretreatment step, especially for fresh leachates.